Preparation of One-page Lesson Plan for German Teachers in Malang - Edy Hidayat; M Kharis; Dewi Kartika Ardiyani; Herri Ahmad Bukhori (Journal of Development Research, 2021)
The one-page lesson plan (LP) is one of four new policies announced by the Indonesian Ministry of Education and Culture several years ago. LP is prepared so that teachers have plenty of time to prepare and evaluate the learning process. The training on how to design a one-page LP provides new experiences for teachers, who are members of the German Teachers Association (IGBJI) in Malang. Based on the results of the questionnaire, more than half of the participants stated that the design of the one-page LP was easier than the old one because the new design had components that were more concise and streamlined, made it efficient in many ways. Although the teachers still have shortcomings, but in general, it can be stated that the use of a one-page LP can help teachers to have an orientation in teaching.